Peranan Pimpinan dalam Meningkatkan Kinerja Anggota pada Sekretariat DPRD Kabuapen Nabire - Petrus Tekege (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
The aim of this research is to find and provide suggestions for the role of leadership in improving performance in the Nabire district DPRD office. The approach method is analytical descriptive, with the main problem being the role of the Regional People's Representative Council (DPRD) of Nabire district and the extent of the performance of the members of the Regional People's Representative Council (DPRD) of Nabire district. The results of the research show that the work of the leadership of the Nabire Regency DPRD has not been maximized, which in the future requires increased knowledge and skills so that service to the community will be good.